The relationship of labor market balance to the industrial cluster in Iraq (Karbala Governorate as a model ) (Journal of the College of Basic Education, 2022)
This research aims to identify the variation in the localization of industrial activities and their role in providing job opportunities at the level of Karbala Governorate. The problem of the study lies in the existence of a variation in the job opportunities provided by the various industrial sector activities between the districts and sub-districts of Karbala Governorate. This discrepancy may be due to the difference in the number of industrial establishments existing between the branches of the industrial sector on the one hand and their size, and number of current jobs provided by the workforce on the other hand, and thus it results from a difference in the added value generated by the industrial production and the wages owed to the workers. The study adopted a descriptive and analytical statistical method in conducting quantitative comparisons between the characteristics of the industrial sector facilities in Karbala Governorate based on some tables, graphs and statistical indicators derived from (location quotients) and importance rates of Industrial establishments sector using the values of transactions quotients, employee wages and added value based on the economic activity of industry in the governorate. The most prominent results of the study were the existence of a difference in the values of value-added coefficient) according to the nature of the quality of their humanitarian the location quotients of establishments (labor coefficient, wages and benefits coefficient, added value coefficient) according to its economic activities. The results also showed that there is a difference in the adjusted proportional distribution of industrial importance according to the industrial activities in the governorate, and the study recommended encouraging investments and directing them towards medium and large-sized industries in terms of their use of labor, especially in economic activities with high levels of location quotients and adopting development policies to develop human resources and raise Its efficiency in the governorate to meet the investors' needs of qualified and trained technical manpower to set up industrial projects therein .